A review of the mechanisms underlying the role of the GIPC3 gene in hereditary deafness - Li, Xinxin; Shi, Lin; Wang, Liang (Frontiers in Synaptic Neuroscience, 2023)
Abstract: The GAIP interacting protein c terminus (GIPC) genes encode a small family of proteins characterized by centrally located PDZ domains. GIPC3 encodes a 312 amino acid protein. Variants of human GIPC3 are associated with nonsyndromic hearing loss. GIPC3 is one of over a hundred different genes with variants causing human deafness. Screening for variants of GIPC3 is essential for early detection of hearing loss in children and eventually treatment of deafness. Accordingly, this paper assesses the status of research developments on the role of GIPC3 in hereditary deafness and the effects of pathogenic variants on the auditory system.